Gender and School Achievement in the Caribbean - Kutnick, Peter; Jules, Vena; Layne, Anthony (Department for International Development, 1997)
This project explored the reasons why females stay-on in schools and gained comparatively better achievement scores in Trinidad, Barbados, and St. Vincent. The four research questions which underlay the studies related to: 1) the variance of within-class achievement scores by sex, especially between students of equal ability (as noted by results of the primary School Leaving examination and the Common Entrance Examination (CEE); 2) whether differential levels of achievement remained over time, especially over the years of secondary schooling; 3) whether there were differential learning strategies that characterised girls and boys in school, and whether these strategies were related to the status of their secondary school; and 4) whether the quantitative results obtained from an earlier Trinidad study could be substantiated elsewhere, especially in Barbados and St. Vincent. Data were collected through quantitative surveys to assess success and generalizability of results from one island to another, and qualitative case studies to provide insights into classroom process, interaction, and structure in the promotion of success at the level where it affected children. The quantitative surveys showed that the average within-class attainment and CEE scores attained by girls was consistently higher that those attained by boys across the three countries. The drop-off in male participation in schooling, especially during the transition to and during secondary schooling, was confirmed in Barbados and St. Vincent. Sex of the children was only one significant factor in the explanation of attainment in school. Factors such as occupation of parents, whether the child lived with both parents, attendance at preschool, and the type of school attended, each contributed more of the variance in attainment than the sex of the child. Within schools, the case studies showed practices that allowed for the inclusion or exclusion of certain children (especially low attainers, a number of whom were male). The culture found in prestige schools overcame sex.
Keywords: Academic achievement